NATURAL CONVECTION IN CONFINED CYLINDRICAL ENCLOSURE OF POROUS MEDIA WITH CONSTANT AND PERIODIC WALL TEMPERATURE BOUNDARY CONDITIONS (Journal of Engineering, 2011)
Numerical investigations of unsteady natural convection heat transfer through a fluid-saturated porousmedia in inclined cylindrical enclosure are studied by solving the governing (3-D) Darcy-Boussinesqequations using finite difference method. The momentum equation of flow was solved by Relaxation method and the energy equation by using Alternating Direction Implicit (ADI) method. The problem is analyzed for modified Rayleigh number with range of (50-300),angles of inclination (0°,25°,45°60°90°), amplitude of sinusoidal temperature (0.2, 0.4, 0.8) and period (0.005, 0.01, 0.02). Results indicate an increase in the heat transfer with increasing of Rayleigh number, time, amplitude, angle of inclination and period. Also average and local Nusselt number were calculated and it is found that Maximum temperature and velocity occur at angle α=45 and this indicate a strong buoyancy force effect on convective flow.